1978
DOI: 10.3758/bf03205086
|View full text |Cite
|
Sign up to set email alerts
|

A feed delivery system for the study of choice behavior in cows

Abstract: A feed delivery system for the study of choice behavior in cows is described. Supportive data are provided for six dairy cows exposed to two-alternative, concurrent variable-interval schedules.Air cylind~r.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1979
1979
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…2. The work of Hollard andDavison (1971) andMiller (1976) has been partially replicated, showing that concurrent VI schedules may provide a useful technique for the quantitative analysis of food preferences in the dairy cow, particularly when measures unconfounded by the postingestional consequences are needed (Cate et al, 1978). Other research in this laboratory using medicated molasses lick-blocks has shown that consistent values of ql/q2 markedly different from 1.00 are obtainable.…”
Section: Discussion Equation 2 With C Constant or Equationmentioning
confidence: 90%
See 1 more Smart Citation
“…2. The work of Hollard andDavison (1971) andMiller (1976) has been partially replicated, showing that concurrent VI schedules may provide a useful technique for the quantitative analysis of food preferences in the dairy cow, particularly when measures unconfounded by the postingestional consequences are needed (Cate et al, 1978). Other research in this laboratory using medicated molasses lick-blocks has shown that consistent values of ql/q2 markedly different from 1.00 are obtainable.…”
Section: Discussion Equation 2 With C Constant or Equationmentioning
confidence: 90%
“…Two square nose-plates, .10 m by .10 m, were mounted .67 m apart on a dual feeddelivery unit (Cate, Mullord, Temple, & Matthews, 1978). The unit was .45 m wide by .90 m long by .80 m high.…”
Section: Apparatusmentioning
confidence: 99%
“…A feed delivery unit with two hoppers, described in detail by Cate, Mullord, Temple, and Matthews (1978), permitted the presentation of equal volumes of two foods. The foods presented in this study were commercially produced crushed barley and meatmeal.…”
Section: Apparatusmentioning
confidence: 99%
“…The key was backlighted with either a red or a white bulb. Subjects received feed from a feed bucket delivered to the subject via a pneumatic ram (Cate et al, 1978), which was controlled either manually or by computer. Initial behavior was shaped by manually providing access to rolled barley in the feed magazine as responses gradually came closer to breaking the light beam (i.e., successive approximations).…”
Section: Methodsmentioning
confidence: 99%